Empowering Saudi Women for Sports as a Response to KSA Vision 2030: Attitudes of Undergraduate Female Students toward Practicing Sports - Mohammed FAKEHY; Ahmed ALFADHIL; Yasser HASSAN; Hend ALOTAIBI, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Background: Paying particular attention to women’s health is of great significance for ensuring the well-being of the general population. One of the key aspects of caring for their health arises is encouraging active engagement in sports, which is undoubtedly an essential pillar of a healthy lifestyle. Sports activities are important for maintaining physical, psychological, mental, and social health. The objective of this study is to identify the factors affecting the attitude of undergraduate female students in Saudi Arabia towards sports. The relationship between physical fitness, social experience, formal competition, physiological experience and sports attitude of female students has been examined in this study. Methods: For the purposes of this study, a questionnaire survey is conducted to study the factors affecting the attitudes of undergraduate female students enrolled in universities of Saudi Arabia regarding sports activities. The study sample consists of 645 female students from various universities of Saudi Arabia. The collected data has been analyzed and processed using Partial Least Square (PLS). Results: Results of the study report that; physical fitness, social experience and formal competition have a positive effect on physiological experience which in turn has a positive effect on the attitude of female students towards sports. Conclusion: Physical fitness, social experience, formal competition, and physiological experience has the ability to promote a more positive attitude towards sports among the female students in Saudi Arabia. Various factors including physical fitness, social experience and formal competition have positive role in promoting better physiological experience which further lead to a more positive attitude among female students towards sports. Hence, the current study has important role for the management of universities to promote sports attitude among undergraduate students.